Tailor-made 3D-nanoelectrode ensembles modified with molecularly imprinted poly(o-phenylenediamine) for the sensitive detection of L-arabitol - Beluomini, Maísa Azevedo [UNESP] (2019)
A highly selective and sensitive sensor for L-arabitol is developed combining the advantages of three-dimensional nanostructrured electrodes, namely, 3D-ensembles of gold nanowires (3DNEE), with the recognition capability of molecularly imprinted polymer (MIP). The MIP/3DNEE is prepared by controlled etching of polycarbonate templated nanoelectrode ensembles, followed by electropolymerization of o-phenylenediamine on the gold nanowires in the presence of L-arabitol as molecular imprinting template. For activating the sensor, L-arabitol is removed from the MIP with an ethanol/water mixture. The sensor is characterized by scanning electron microscopy and dispersive energy X-ray spectroscopy while its electrochemical properties are examined by cyclic voltammetry, differential pulse voltammetry and electrochemical impedance spectroscopy. Analytically usefull signals are obtained using the ferrocenylmethytrimethylammonium cation as an electroactive probe which can access the MIP cavities, furnishing voltammetric signals which scale inversely with the L-arabitol concentration. The sensor is characterized by a low detection limit (7.5 × 10−10 mol L-1), satisfactory quantification range, selectivity, reproducibility and repeatability. The applicability of the MIP/3DNEE in real samples is demonstrated by successfully quantifying L-arabitol concentration in sugarcane vinasse.